Еволюція поглядів на державне регулювання галузей сільського та рибного господарства в аспекті забезпечення конкурентоспроможності продукції на ринку - Каліна Ірина; Kalina Irina; Пойда-Носик Ніна; Poyda-Nosyk Nina; Pojda-Noszik Nina (Львівський Університет Бізнесу та Права, 2022)
Резюме. У статті доведено, що з появою нових технологій, змінами в економічній політиці та ринкових умовах, регулювання в галузях сільського та рибного господарства потребує безпосередньої адаптації до зростаючих викликів і можливостей. Обґрунтовано, що одним із засадничих аспектів даного процесу є державне регулювання, яке спрямоване на забезпечення ефективності та конкурентоспроможності сільськогосподарської продукції на ринку, включаючи продукцію равликівництва, аквакультури та рибного господарства. З урахуванням посилення ролі держави запропоновано методичні підходи до створення конкурентоспроможного виробництва продукції тваринництва й підтримки провідних галузей аграрного сектора економіки.

Abstract. In recent years, the evolution of views on state regulation of agriculture and fisheries has become the subject of active discussions and research. Significant transformations in the economy and the global market environment call for the need to review and adapt the strategies of state intervention, in particular, in activities in the formation of demand and supply for snail farming and aquaculture products. This is especially relevant in the context of ensuring the competitiveness of products on the market, which is an important condition for the sustainable development of the agricultural and fishery industries. In this context, it is important to analyze the stages and trends in the evolution of approaches to state regulation of these industries, to evaluate and determine their impact on the competitiveness of manufacturers. Currently, the work of economists is focused on the creation of competitive agricultural production, which is impossible without strengthening the role of the state and supporting the leading branches of the agricultural sector of the Ukrainian economy. The article proves that with the emergence of new technologies, changes in economic policy and market conditions, regulation in the fields of agriculture and fisheries requires immediate adaptation to growing challenges and opportunities. It is substantiated that one of the fundamental aspects of this process is state regulation, which is aimed at ensuring the efficiency and competitiveness of agricultural products on the market, including products of snail farming, aquaculture and fisheries. Taking into account the strengthening of the role of the state, methodical approaches to the creation of competitive production of animal husbandry products and support of the leading branches of the agrarian sector of the economy are proposed.
Редакційна колегія: https://nzlubp.org.ua/index.php/journal/about/editorialTeam
Зміст: https://nzlubp.org.ua/index.php/journal/issue/view/19
Keywords: державне регулювання; ринок; інструменти; попит; метод; механізм; тваринництво; пропозиція; рибне господарство; равликівництво; аквакультура; продукція; галузь; риба; конкурентоспроможність; національна економіка; імпорт; експорт; government regulation; market; tools; demand; method; mechanism; animal husbandry; supply; fisheries; snail; farming; aquaculture; products; industry; fish; competitiveness; national economy; import; export